EFFICACY OF PROPHYLACTIC INTRAWOUND APPLICATION OF VANCOMYCIN POWDER IN PREVENTING SURGICAL SITE INFECTIONS IN SPINAL INSTRUMENTATION SURGERY - Khalid, Shah; Shahbaz Ali Khan,; Attiya Nasir,; Gul Muhammad,; Faiza,; Muhammad Adeel Alam,; Zanib Javed ,; Abdul Majid Khan,; Tariq Rahim,; Ahsan Aurangzeb, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Surgical site infection (SSI) is always a matter of utmost concern in cases of spinal instrumentation in low-income countries. This study was conducted to determine the efficacy of local intrawound application of vancomycin powder in reducing postoperative SSI following Thoracolumbar-Sacral spinal instrumentation. Methods: This randomized controlled trial was done in the Department of Neurosurgery, Ayub Teaching Hospital Abbottabad from 1st July 2019 to 31st December 2021. Seventy-eight patients of either gender with an age range from 15 to 65 years, who were planned for posterior spinal instrumentation surgery (transpedicular screw fixation), were included in the study. Patients were divided into two equal groups, A (Vanco group) and B (control group). In addition to standard systemic prophylaxis, 1 gm of Vancomycin powder was applied over the implant in Group A patients. Results: The mean age of the patients in Group A was 36±16.6 while the mean age of patients in the group was 33.7±15.9 years. A statistically significant reduction of surgical site infection was observed in those who received a prophylactic intra-wound application of vancomycin powder (Vanco group) (5.2%) compared to the control group (20.5%). Conclusion: Intrawound vancomycin powder administration significantly decreases SSI following spinal instrumentation surgeries. Patients at high risk of infection are highly recommended as a candidate for this technique.